Analisis daya dukung ekowisata birdwatching di Taman Wisata Alam Gunung Tunak, Lombok, Nusa Tenggara Barat - Sulastri, Sastia; Farista, Baiq; Suana, I Wayan (Jurnal Biologi Udayana; Vol 27 No 2 (2023): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2023.v27.i02.p02, 2023)
Gunung Tunak Nature Tourism Park (GTNTP) is a conservation area in Lombok, West Nusa Tenggara, used for nature tourism and recreation activities. GTNTP has a high diversity of bird species, so it has great potential to be developed into birdwatching ecotourism. Ecotourism activities have a negative impact on the environment if the number of tourists exceeds the carrying capacity. Tourism planning that does not pay attention to carrying capacity sooner or later will lower environmental quality and cause ecological damage, affecting the presence of birds and other wildlife in that location. Carrying capacity calculations need to be carried out to protect the conservation function of GTNTP and maintain environmental sustainability. This research aims to analyze the carrying capacity of birdwatching ecotourism based on biophysical and management aspects at GTNTP. The tourism carrying capacity assessment method was carried out in three stages, namely physical carrying capacity (PCC), real carrying capacity (ECC), and effective carrying capacity (ECC). The biophysical aspects considered in this research were breeding sessions of birds, rainfall, slope, and soil sensitivity to landslides. The result showed that the PCC observation trail to the gateway (MPM) was 2,527 visitors/day and the observation trail to the Teluk Ujung Beach (MPTU) was 1,408 visitors/day. The RCC MPM observation trail has 245 visitors per day, and the MPTU trail has 315 visitors per day. The ECC, by paying attention to physical, ecological, and management aspects on the MPM observation trail was 178 visitors per day, and the MPTU trail is 229 visitors per day. Based on the ECC value, the future development of birdwatching ecotourism in GTNTP can be optimized by 83.38% (162 visitors per day or 4,860 visitors per month). For the MPM trail and 93.01% for the MPTU trail (213 visitors/day or 6,390 visitors/month).